Guidance on the assessment of the biological relevance of data in scientific assessments. (3rd August 2017) - ,; Hardy, Anthony; Benford, Diane; Halldorsson, Thorhallur; Jeger, Michael John; Knutsen, Helle Katrine; More, Simon; Naegeli, Hanspeter; Noteborn, Hubert; Ockleford, Colin; Ricci, Antonia; Rychen, Guido; et al.
Abstract: EFSA requested its Scientific Committee to prepare a guidance document providing generic issues and criteria to consider biological relevance, particularly when deciding on whether an observed effect is of biological relevance, i.e. is adverse (or shows a beneficial health effect) or not. The guidance document provides a general framework for establishing the biological relevance of observations at various stages of the assessment. Biological relevance is considered at three main stages related to the process of dealing with evidence: Development of the assessment strategy. In this context, specification of agents, effects, subjects and conditions in relation to the assessment question(s): Collection and extraction of data; Appraisal and integration of the relevance of the agents, subjects, effects and conditions, i.e. reviewing dimensions of biological relevance for each data set. A decision tree is developed to assist in the collection, identification and appraisal of relevant data for a given specific assessment question to be answered. Abstract : This publication is linked to the following EFSA Supporting Publications article:http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2017.EN-1296/full